Reach-to-Grasp: A Multisensory Experience - Betti, Sonia; Castiello, Umberto; Begliomini, Chiara (Frontiers in Psychology, 2021)
The reach-to-grasp movement is ordinarily performed in everyday living activities and it represents a key behavior that allows humans to interact with their environment. Remarkably, it serves as an experimental test case for probing the multisensory architecture of goal-oriented actions. This review focuses on experimental evidence that enhances or modifies how we might conceptualize the ‘multisensory’ substrates of prehension. We will review evidence suggesting that how reach-to-grasp movements are planned and executed is influenced by information coming from different sensory modalities such as vision, proprioception, audition, taste and olfaction. The review closes with some considerations about the predominant role of the multisensory constituents in shaping prehensile behavior and how this might be important for future research developments, especially in the rehabilitative domain.